Effects of surface treatments of conventional glass-ionomer on shear bond strength to giomer - Soodabeh Kimyai; Narmin Mohammadi; Parnian Alizadeh Oskoee; Mohammad Esmaeel Ebrahimi Chaharom; Mahmood Bahari; Alireza Sadr; Ghazaleh Ahmadizenouz (Wolters Kluwer Medknow Publications, 2012)
Background : An appropriate bond between glass-ionomer and the superficial resin materials is very important for the success of sandwich technique. The aim of the present in vitro study was to evaluate the effect of three surface treatments of conventional glass-ionomer on its shear bond strength to giomer. Materials and Methods: Sixty cylindrical specimens of a conventional glass-ionomer (GC Fuji II) were prepared and randomly divided into three groups (n = 20). The specimens in groups 1 and 2 were treated with total-etch adhesive resin (Single Bond) along with acid etching, and self-etch adhesive resin (FL-Bond II) on the set glass-ionomer, respectively. Specimens in group 3 were treated with self-etch adhesive resin (FL-Bond II) before initial setting of the glass-ionomer was complete. Then a giomer restorative (Beautifil II) was added to the specimens. Subsequent to thermocycling, the specimens were subjected to shear bond strength test. Failure modes were evaluated under a stereomicroscope. Data were analyzed by one-way analysis of variance and a post hoc Tukey test at a significance level of P < 0.05. Results: There were statistically significant differences in bond strengths between the groups (P < 0.0005). Differences in bond strengths between group 2 and other groups were significant (P < 0.0005) while the differences between groups 1 and 3 were not significant. Failures were predominantly of the cohesive type in all the groups. Conclusion: Based on the results of this study, the use of self-etch adhesive resin (FL-Bond II) on the set glass-ionomer yielded the highest bond strength in the glass-ionomer/giomer sandwich technique.